Clinical Management of Paraphimosis in a Mongrel Dog: A Case Report - Kandhikonda, Sravika; Golusu, Sai Charan; K, Vaibhavi; Kudikilla, Venkata Ramana; Komatireddy, Ramachandra Reddy; Kodidanti, Chandrasekhar Reddy; Lakavath, Ramsingh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present case deals with clinical management of paraphimosis in 1 year old mongrel dog Presented to Teaching veterinary Clinical Complex. After thorough clinical examination the protruded penis was cleaned and antiseptic dressing was done. Then edema was reduced by applying Hypertonic solution D25 (25 percent dextrose solution) and ice packs. Once the swelling had sufficiently decreased, the area was cleaned again Lignocaine gel was applied topically for pain management and lubrication, allowing for a gentle repositioning of the penis into the preputial sheath Prognosis was good. No further complications were observed.